Neuropeptide Y in Alcohol Addiction and Affective Disorders - Thorsell, Annika; Mathé, Aleksander A. (Frontiers in Endocrinology, 2017)
Neuropeptide Y (NPY), a neuropeptide highly conserved throughout evolution, is present at high levels in the central nervous system (CNS), as well as in peripheral tissues such as the gut and cardiovascular system. The peptide exerts its effects via multiple receptor subtypes, all belonging to the G-protein coupled receptor superfamily. Of these subtypes, the Y1 and the Y2 are the most thoroughly characterized, followed by the Y5 subtype. NPY and its receptors have been shown to be of importance in central regulation of events underlying, for example, affective disorders, drug/alcohol use disorders, and energy homeostasis. Furthermore, within the CNS, NPY also affects sleep regulation and circadian rhythm, memory function, tissue growth and plasticity. The potential roles of NPY in the etiology and pathophysiology of mood and anxiety disorders, as well as alcohol use disorders, have been extensively studied. This focus was prompted by early indications for an involvement of NPY in acute responses to stress, and, later, also data pointing to a role in alterations within the CNS during chronic, or repeated, exposure to adverse events. These functions of NPY, in addition to the peptide’s regulation of disease states, suggest that modulation of the activity of the NPY system via receptor agonists/antagonists may be a putative treatment mechanism in affective disorders as well as alcohol use disorders. In this review, we present an overview of findings with regard to the NPY-system in relation to anxiety and stress, acute as well as chronic; furthermore we discuss post-traumatic stress disorder (PTSD) and, in part depression. In addition, we summarize findings on alcohol use disorders and related behaviors. Finally, we briefly touch upon genetic as well as epigenetic mechanisms that may be of importance for NPY function and regulation. In conclusion, we suggest that modulation of NPY-ergic activity within the CNS, via ligands aimed at different receptor subtypes, may be attractive targets for treatment development for affective disorders, as well as for alcohol use disorders.